2019
DOI: 10.24841/fa.v27i1.435
|View full text |Cite
|
Sign up to set email alerts
|

Estudio De Viabilidad Y Conservación De Semillas De Cinco Especies Vegetales Amazónicas Como Base Para La Creación De Un Banco De Germoplasma en El Municipio De Leticia, Amazonas, Colombia

Abstract: Como parte del proceso para el establecimiento de un banco de germoplasma de especies amazónicas maderables y no maderables que contribuyen a la seguridad alimentaria del municipio de Leticia, Amazonas (Colombia), fue realizada la caracterización de once especies vegetales que consistió en la definición de usos, períodos de fructificación y experiencias de propagación, durante el período de junio a octubre de 2017; para avanzar con el análisis de factores que afectan directamente el comportamiento al almacenam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
2
2
1
1
Order By: Relevance
“…The seed weight of C. guianensis varied within a broad range (i.e., from 23.36g to 49.60g), with an average of 35.7g. This value is higher than reported by Hernández-Coronado et al (2018), who found an average weight of 22.1g based on 100 seeds. Similarly, Kossmann et al (2002) reported weights between 25 and 32g and established that 30-50 seeds are required to obtain 1kg.…”
Section: Resultscontrasting
confidence: 70%
See 1 more Smart Citation
“…The seed weight of C. guianensis varied within a broad range (i.e., from 23.36g to 49.60g), with an average of 35.7g. This value is higher than reported by Hernández-Coronado et al (2018), who found an average weight of 22.1g based on 100 seeds. Similarly, Kossmann et al (2002) reported weights between 25 and 32g and established that 30-50 seeds are required to obtain 1kg.…”
Section: Resultscontrasting
confidence: 70%
“…For C. guianensis¸ germination behavior is variable; for instance, 24% to 90% germination can be reached in different periods ranging from days to months (Kossmann et al, 2002;Amaral et al, 2017;Hernández-Coronado et al, 2018). Therefore, nursery propagation alternatives for this species have led to the use of different pre-germination treatments such as mechanical scarification, sunlight exposure, and seed imbibition in sand and soil substrates (Torres et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…accordingly, T4 in S1 showed the highest germination percentage than other substrates and treatments. Overall, C. guianensis was found to germinate gradually, which agrees with reports byVillota (2016) andHernández-Coronado et al (2018).…”
supporting
confidence: 92%
“…Therefore, information about germination dynamics and seed morphology are important to establish seed collection and management guidelines to successfully propagate this species (Abbade and Takaki, 2014;Peixoto et al, 2019). For C. guianensis¸ germination behavior is variable; for instance, 24% to 90% germination can be reached in different periods ranging from days to months (Kossmann et al, 2002;Amaral et al, 2017;Hernández-Coronado et al, 2018). Therefore, nursery propagation alternatives for this species have led to the use of different pre-germination treatments such as mechanical scarification, sunlight exposure, and seed imbibition in sand and soil substrates (Torres et al, 2017).…”
Section: Palabras Clavementioning
confidence: 99%
“…En el caso de las semillas no germinadas y no depredadas, los bajos porcentajes de germinación pueden deberse, entre otras causas, a que estas especies presentan semillas recalcitrantes, por tanto, requieren de las condiciones adecuadas para germinar. Asimismo, las semillas de estas palmas requieren de procesos de escarificación para su pronta germinación [30].…”
Section: Especieunclassified